Application of Integrated Emergency Care Model Based on Failure Modes and Effects Analysis in Patients With Ischemic Stroke - Yang, Yuying; Chang, Qing; Chen, Jing; Zou, Xiangkun; Xue, Qian; Song, Aixia (Frontiers in Surgery, 2022)
Purpose: To explore the application value of an integrated emergency care model based on failure modes and effects analysis (FMEA) in patients with acute ischemic stroke (AIS). Methods: According to the convenience sampling method, 100 patients with AIS who visited the emergency department in our hospital from October 2018 to March 2019 were randomly selected as the control group and received routine emergency care mode intervention. Another 100 AIS patients who visited the emergency department from April to October 2019 were selected as the intervention group and received the integrated emergency care model based on FMEA. The total time spent from admission to completion of each emergency procedure [total time spent from admission to emergency physician (T0-1), total time spent from admission to stroke team (T0-2), total time spent from admission to imaging report (T0-3), total time spent from admission to test report (T0-4), and total time spent from admission to intravenous thrombolysis (T0-5)] was recorded for both groups. The clinical outcome indicators (vascular recanalization rate, symptomatic intracerebral hemorrhage incidence, mortality rate) were observed for both groups. The NIHSS score and Barthel score were evaluated for both groups after the intervention. The treatment satisfaction rate of the patients was investigated for both groups. Results: The total time of each procedure in the intervention group was shorter than that in the control group, the vascular recanalization rate was better than that of the control group, the NIHSS score was lower than that of the control group, the Barthel score was higher than that of the control group, and the treatment satisfaction rate was higher than that of the control group (P<0.05). There was no statistical significance in the symptomatic intracerebral hemorrhage incidence and mortality rate in the two groups (P>0.05). Conclusion: Through FMEA, the failure mode that affects the emergency time of AIS patients is effectively analyzed and the targeted optimization process is proposed, which are important to enhance the efficiency and success rate of resuscitation of medical and nursing staff and improve the prognosis and life ability of patients.